Antimicrobial, Antioxidative and Antilymphoproliferative Activity of a New Protein (INDIN-SAA) Isolated from Roots of Boerhaavia diffusa (Punarnava) against Scrofula adenitis (Anjeerbal) - Chandel4 and M Salman Khan1,5, Amir Khan1,2,*, Fouzia Ishaq3, Abhay S (Recent Research in Science and Technology, 2011)
The aim of this present study was to investigate the antimicrobial, antioxidative and antilymphoproliferative activity of the isolated new INDIN-SAA protein from the roots of B. diffusa against the disease scrofula adenitis caused by Mycobacterium scrofulaceum. Total antioxidant capacity assay showed that purified protein fraction (PPF) show stronger antioxidant activity (3.15 fold vs CPE-1.34 fold vs PPPE), than partially purified protein fraction (PPPF) and crude protein extract (CPE), respectively. The antimicrobial activity of the isolated CPEs and its PPFs on the pathogen M. scrofulaceum was evaluated on the basis of inhibition zone (IZ) using hole diffusion method, the minimal inhibitory concentration (MIC) and bacterial growth curve inhibition. The data showed that significant antimicrobial and antioxidative effect of the crude protein and its purified fractions against microorganism (M. scrofulaceum). Thus the result of this study could provide efficacious and cost effective treatment of the disease (Scrofula adenitis) without any cytotoxic effects.